Performance Analysis of Cooperative Vehicular Systems with Co-channel Interference Over Cascaded Nakagami-m Fading Channels - Ilhan, Haci (SPRINGER, 2015)
In this paper, we investigate a dual-hop decode-and-forward (DF) relaying vehicular system in the presence of co-channel interference, in which source, relay and destination terminals are composed of vehicles and interferers are stationary. Independently but not necessarily identically distributed (i.n.i.d.) cascaded Nakagami-m fading is adopted to characterize the vehicle-to-vehicle channel. Novel closed-form expressions are derived for cumulative distribution function (CDF) of end-to-end signal-to-interference-plus-noise-ratio at the relay and the destination. By using CDF expressions, we have analyzed the performance of dual-hop DF relaying vehicular systems in terms of outage probability and average symbol error probability. Then, we have calculated the upper bounds of outage probability and symbol error probability expressions for high signal-to-noise ratio. Lastly, the effect of relay geometry on system performance has been examined. The proposed mathematical analyses have been verified through the Monte-Carlo simulations.
Keywords: Co-channel interference; Cascaded Nakagami-m fading channels; Outage probability; Symbol error probability; Dual-hop decode-and-forward relaying; N-ASTERISK-NAKAGAMI; FORWARD SYSTEMS; TRANSMISSIONS; DIVERSITY; SELECTION; NETWORKS; RELAY; Telecommunications